Perencanaan Strategis TI Menggunakan Metode Ward and Peppard pada Dispora Kota Palembang - Saputra, Michael; Pratama, Dicky (Universitas Multi Data Palembang, 2025)
The Palembang City Youth and Sports Agency faces challenges in utilizing information technology to improve operational efficiency and the quality of public services. This study aims to formulate strategic information technology planning using the Ward and Peppard framework. The analytical approaches used include Value Chain to identify primary and supporting activities in the organization, PEST Analysis to assess external factors that affect the organization, SWOT Analysis to identify strengths, weaknesses, opportunities, and threats, Critical Success Factors (CSFs) is used to determine key success factors for implementing IS/IT strategies, and McFarlan Strategic Grid is used to group applications based on their level of importance to the organization. The results of this study include a portfolio of future applications that support system integration, resource optimization, and increasing the organization's digital capabilities. The implementation of the IS/IT strategy is designed to align with the organization's priority needs, such as the development of a digital-based sports management system. It is hoped that this strategic planning can help the Palembang City Youth and Sports Agency achieve operational excellence and improve the quality of service to the community.